The Influence Of Customer Trust And Corporate Reputation On Customer Loyality With Customer Satisfaction As a Moderating Variable at Bank Syariah Indonesia BSI KCP Rumbai Pekanbaru - Handayani, Widya; Wijayanto, Gatot; Restuti, Sri (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
The presence of PT Bank Syariah Indonesia Tbk (BSI) in the Rumbai area with the aim of optimizing services and synergy with the community in financial transactions according to sharia principles for the local community. In May 2023, BSI customer data was leaked after previously experiencing a ransomware attack. This raises concerns for BSI customers. Customer data leaks are a serious problem that can damage a company's reputation. These concerns can lead to decreased trust and reduced consumer loyalty to the company. This research aims to see the influence of customer trust and company reputation on customer loyalty with customer satisfaction as a moderating variable at BSI Pekanbaru Rumbai branch office. The population in the study were all customers of BSI Rumbai Pekanbaru branch office, totaling 15,858 customers. Meanwhile, the sampling technique uses the Isaac and Michael formula with an alpha of 5%. And a sample of 376 customers was obtained. The data analysis method used is Structural Equation Model (SEM) using SmartPLS software. The test results show that customer trust and company reputation have a significant effect on customer loyalty. Then also customer satisfaction significantly moderates the influence of customer trust and company reputation on customer loyalty. The magnitude of the influence of customer trust and company reputation on customer loyalty is moderated by customer satisfaction at 71.8%.